Forage Yield and Quality of Sweet Sorghum as Influenced by Sowing Methods and Harvesting Times - Muhammad Umer Chattha; Aisf Iqbal; Muhammad Umair Hassan; Muhammad Bilal Chattha; Wajid Ishaque; Muhammad Usman; Sadia Khan; Muhammad Tauqir Fayyaz; Muhammad Aman Ullah (Journal of Basic & Applied Sciences, 2017)
Sowing methods and harvesting times are the important management considerations for getting the optimum yield and quality of fodder crops. This study, investigated the influence of sowing methods and harvesting times on the growth, yield and quality of sweet sorghum. Chinese sweet sorghum was grown by broadcast method, 30 cm apart lines and 45 cm apart lines and harvested after 60, 75 and 90 days after sowing, respectively. All the tested sowing patterns and harvesting times considerably affected the growth, yield and quality of sweet sorghum. However, sowing in 30 cm apart rows produced maximum leaves per plant (13.09), fresh forage yield (38.1 t ha-1), dry matter yield (4.85 t ha-1), crude proteins (8.9%), ash contents (11%) and sugar contents (12.8%), respectively. Similarly, harvesting after 90 days of sowing gave highest leaves per plant (14.72), fresh forage yield (45.1 t ha-1), dry matter yield (5.60 t ha-1), ash contents (12.2%) and sugar contents (14.1%), respectively. These results suggested that sowing in 30 cm apart lines and harvesting after 90 days of sowing improved the growth, yield and quality of sweet sorghum under the semiarid region of Faisalabad.